Non-suicidal self-injury and suicidal ideation as predictors of suicide attempts in adolescent girls: A multi-wave prospective study - Lori N. Scott; Paul A. Pilkonis; Alison E. Hipwell; Kate Keenan; Stephanie D. Stepp (Comprehensive Psychiatry, 2015)
Although both suicide ideation (SI) and non-suicidal self-injury (NSSI) are known risk factors for suicidal behavior, few longitudinal studies have examined whether having a history of one or both of these factors prospectively predicts increased risk for suicide attempts. According to the theory of acquired capability for suicide, engagement in NSSI may reduce inhibitions around self-inflicted violence, imparting greater risk for suicide attempts among those with SI than would be observed in those with SI who do not have a history of NSSI. We used prospective data from the Pittsburgh Girls Study, a large community sample, to compare groups of girls reporting no SI or NSSI, SI only, or both NSSI and SI between early to late adolescence on any lifetime or recent suicide attempts in late adolescence and early adulthood. As compared to girls with no SI or NSSI history and those with only an SI history, girls with a history of both NSSI and SI were significantly more likely to subsequently report both lifetime and recent suicide attempts. Results are consistent with the acquired capability theory for suicide and suggest that adolescent girls who have engaged in NSSI and also report SI represent a particularly high-risk group in need of prevention and intervention efforts.